Metacromasia para identificação de basófilos sanguíneos em surubim híbrido: contribuição metodológica - de Padua, Santiago Benites [UNESP] (2011)
Padua S.B. & Ishikawa M.M. [Metachromasia for blood basophils identification in hybrid surubim catfish: methodological contribution]. Metacromasia para identificacao de basofilos sanguineos em surubim hibrido: contribuicao metodologica. Revista Brasileira de Medicina Veterinaria, 33(3):147-150, 2011. Centro de Aquicultura da Unesp/Jaboticabal Rod. Paulo Donato Castellane, s/n Bairro Rural, Jaboticabal, 14884-900, SP. Brasil. E-mail: santiagopadua@live.comDifferent protocols of fixation and hydrolysis of blood smears of hybrid surubim catfish for metachromasia to marking blood basophils were evaluated. For this reason, methanol, acid-alcohol and formalin vapor were tested as fixatives. For hydrolysis of blood smears, HCl, citric acid and 2-Mercaptoethanol + Urea + NaCl solutions was evaluated. After procedures, the blood smears was stained with toluidine blue (0.025%) diluted in McIlvaine buffer (pH 4). The different protocols for fixation and hydrolysis of blood smears for metachromasia influenced the quality of the reaction. Hydrolysis with 2-Mercaptoethanol + Urea + NaCl solutions provided negative results when using methanol and acid-alcohol as fixatives. The fixation with acid-alcohol associated with citric acid hydrolysis provides highest quality reason.